Implementasi Besaran Bunga Peer to Peer Lending Berdasarkan Asas Itikad Baik dalam Pemanfaatan Teknologi Informasi Serta Pengawasannya - Anita Khoirunisa; Agus Suwandono; Helitha Novianty Muchtar (Widya Yuridika, 2020)
Peer to Peer Lending (“P2P Lending”) is one of financial technology products as financing alternative for public. The execution of P2P Lending is under supervision of OJK which regulated in POJK Number 77/POJK.01/2016. OJK appointed AFPI as OJK’s strategic partner who is authorized to make regulations on the execution of P2P Lending for Providers which accommodated in Code of Conduct formed by AFPI. In brief, this Code of Conduct contains rules that have not been accommodated in POJK Number 77/POJK.01/2016, which interest rates regulation is a part of the Code of Conduct. Interest rates in P2P Lending only accommodated in Code of Conduct, but it has not been well obeyed by the Providers because there are still infringement in determining the interest rates which exceed the predetermined standard with the unclear interest rate information notice. Therefore, this article aims to analyse the application of P2P Lending interest rates which only regulated in Code of Conduct. Furthermore, researcher will also analyse the utilization of information technology in P2P Lending to find out whether the implementation of P2P is in accordance with the good faith principle of the use of information technology in Law Number 11 of 2008 concerning Information and Electronic Transactions. The results of this legal research indicate that OJK are expected to set loan interest rates in P2P Lending individually so that it can provide legal certainty for each party in P2P Lending which impacts on the implementation of P2P Lending.